The impact of public participation on the perception of service quality with the moderating effect of organizational culture in local government in Thailand / Onuma Suphattanakul - Suphattanakul, Onuma (Universiti Teknologi MARA, Shah Alam, 2014)
The purposes of this study are; first, to examine the impact of public participation on the perception of service quality of local government officials; and second, to investigate how organizational culture moderates the impact of public participation on the perception of service quality of local government officials. This is a case study of municipalities in Southern Thailand and a survey data via mail was used. The target population is administrative officials. The data were analyzed by Pearson correlation, linear regression, and hierarchical regression in order to investigate the relationship between variables and to test the hypotheses. This study contributes to the existing body of knowledge by integrating the public management and marketing approaches. The results show that there was a significant positively impact between public participation and the perception of service quality of local government officials. While, the moderating effect of organizational culture was found not significant.